Impact of Organisational Leadership Style on Company Culture-An analysis of SMEs from the Middle East in Bahrain and the UAE - Jayasundera, Aloma; Jackson, Pam (Journal of Ecohumanism, 2024)
This research investigates leadership styles and organisational cultures in Small and Medium Enterprises (SMEs) in Bahrain and the United Arab Emirates (UAE). Through a pre-designed semi-structured survey questionnaire, 200 participants from various disciplines in Bahrain and the UAE (each) provided data. The questionnaire addressed six leadership and four cultural and organisational contexts, exploring two key questions – 1) leadership style and 2) organisational culture in the organisation and demographics. Data analysis tools used in this research included Excel countifs, sum and data analytics available to Microsoft 365 users. The results showed that leadership styles and organisational culture vary across Bahrain and UAE SMEs. Results also evidenced that organisational culture does not affect the performance of SMEs in Bahrain and the UAE. Additionally, results showed that the relationship between leadership style and organisational culture in SMEs in Bahrain and the UAE exists but is not consistently significant.